2007
DOI: 10.1002/cphc.200700236
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Fouling of Nanofiltration Membranes: Measurements and Mechanisms

Abstract: Fouling of nanofiltration membranes is studied during filtration of aqueous surfactant solutions under different conditions. To this purpose, four typical nanofiltration membranes (Desal51HL, NF270, NTR7450 and NFPES10) and three typical surfactants (nonionic neodol, anionic SDBS and cationic cetrimide) are selected. Fouling is studied as a function of the surfactant concentration, with and without addition of an electrolyte (NaCl), at different pH and when filtering a mixture of surfactants. Adsorption experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 37 publications
(63 reference statements)
5
76
0
1
Order By: Relevance
“…The more hydrophilic the membrane is, the tighter the hydrophobic end group of cation surfactant adsorbed on the membrane surface. Similar process can be found in other literatures [36].…”
Section: Membrane Fouling Using Cation Surfactant Aqueous Solutionsupporting
confidence: 75%
“…The more hydrophilic the membrane is, the tighter the hydrophobic end group of cation surfactant adsorbed on the membrane surface. Similar process can be found in other literatures [36].…”
Section: Membrane Fouling Using Cation Surfactant Aqueous Solutionsupporting
confidence: 75%
“…However, above the CMC, concentration polarization by retained micelles causes permeate flux reduction. Kaya et al (2006) and Boussu et al (2007) demonstrated that the adsorption of anionic surfactants on the surface of negatively charged membranes is due to hydrophobic attraction, which is stronger than electrostatic repulsion. Due to the negative membrane charge, the hydrophobic tails are oriented towards the membrane surface and the hydrophilic heads towards the aqueous 3.0 Â 10 À5 4.8 Â 10 À5 40 3.5 Â 10 À5 6.4 Â 10 À5 60 4.3 Â 10 À5 7.9 Â 10 À5 70 4.6 Â 10 À5 9.0 Â 10 À5 80 9.9 Â 10 À5 phase, which results in a more hydrophilic membrane.…”
Section: Nanofiltration Of Contaminated Single-phase Detergents: Shormentioning
confidence: 98%
“…Therefore, at the pH values considered in this work they have a weak negative surface charge. A few authors (Cornelis et al, 2005;Boussu et al, 2007;Kaya et al, 2006Kaya et al, , 2009 investigated the nanofiltration of solutions containing surfactants and they concluded that permeability is strongly influenced by the membrane material and the feed conditions (pH, concentration, etc.). The best results in terms of permeability were obtained with hydrophilic membranes.…”
Section: Nanofiltration Of Contaminated Single-phase Detergents: Shormentioning
confidence: 99%
See 1 more Smart Citation
“…If surfactants are below their critical micelle concentration (CMC) they will not be retained by any of these techniques, but if they are above CMC, MF and UF techniques retain these components and the permeate stream will lose its cleaning properties. Some works based on NF processes with the aim of surfactants recovery in the permeate stream have been published in the last years (Boussu et al, 2007, Forstmeier et al, 2002Kaya et al, 2006Kaya et al, , 2009. In those cases permeate flux and surfactant rejection are strongly dependent on the membrane material (membrane isoelectric point -IEP) and feed conditions (pH, concentration, etc.)…”
Section: Recovery Of Cleaning-in-place Solutionsmentioning
confidence: 99%